The influence of service quality and employee quality on customer’s loyalty towards hotels in Perlis during COVID-19 pandemic / Nurfatin Nabiela Md Noor ... [et al.] - Md Noor, Nurfatin Nabiela; Mohd Said, Noraslinda; Lahap@Wahab, Johanudin; Abdul Hakim, Fairuz; Rahim, Noraini (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Malaysian hotels have suffered significant revenue losses because of the COVID-19 outbreak. As numerous different courses of action were pursued, including firing staff, closing hotels temporarily or permanently, and—in the worst case— filing for bankruptcy, many businesses were discovered to need to restructure their operations. By meeting customers' expectations, requirements, and wants, hotel owners can lessen the impact of the problem by altering their approach to client retention. The purpose of this study is to examine the effects of personnel and service quality on patron loyalty to Perlis hotels during the COVID-19 pandemic. Utilising quantitative techniques, a descriptive cross-sectional study was carried out. Google Forms was utilised by researchers to create and distribute electronic survey questionnaires. Researchers distributed their surveys through internet channels like Facebook, WhatsApp, and Telegram using electronic survey questionnaires created using Google Forms. Out of the 111 surveys that were issued, a total of 107 replies were gathered, representing 69.15% of respondents. The research's outcomes and conclusions were discussed, and they are crucial for a hotel's sustainability.